Panlihi beliefs and practices sa pagbalhin ug balay in Ormoc City, Leyte - Arong, Jonnel A. (1998)
Panlihi beiefs and practices in transferring to a new house are observed and are being performed by certain households and individuals in Ormoc City. There are a total of fifteen respondents who were interviewed who also varied in age and sex. Data were gathered through interview methods and participant-observation technique. The researcher was able to identify ritual elements and objects that are used in performing the rite and their corresponding beliefs, uses, function, and implications that are associated with the act. The researcher also found out that most of the respondents who performed the panlihi truly believe in the good nature that it brings by this folk tradition and not only customarily or for the sake of tradition.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social science